Happy Gilmore - Dugan, Dennis, 1946-; Covert, Allen, 1964-; Carl Weathers; Christopher McDonald; Frances Bay; Julie Bowen; Robert Smigel; Adam Sandler (USA Brillstein-Grey Entertainment, 1996)
A Hockey player wannabe finds out that he has the most powerful golf drive in history. He joins the P.G.A. tour to make some money to save grandma's house. The downside is that his hocky player mentality doesn't really go on the P.G.A. tour. Especially with the favorite to win the championship.
A rejected hockey player puts his skills to the golf course to save his grandmother's house.
Tim Herlihy
Language(s): English, French Subtitle(s): English, Spanish
Keywords: Sport; Comedy